Analisis Etika Bisnis Islam Dan Lebelisasi Halal Dalam Pengambilan Keputusan Pembelian Produk Melalui E-Commerce (Studi Kasus Pada Mahasiswa UIN KH. Abdurrahman Wahid Pekalongan) - Aulia, Fira; Adinugraha, Hendri Hermawan (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This research aims to identify and test the influence of Islamic business ethics and halal certification on purchasing decisions through e-commerce. The method used in this research is a quantitative approach. The independent variables in this research are Islamic business ethics (X1) and halal certification (X2). Meanwhile, the dependent variable in this research is purchasing decisions (Y). Data collection was carried out by distributing questionnaires with a total of 40 respondents who were students of UIN K.H Abdurrahman Wahid Pekalongan. Data processing techniques were carried out using Eviews12. The analysis of this research includes the Classic Assumption Test and Multiple Linear Regression Analysis, t test, f test, and R2 test. Based on the results of the variable significance test, it shows that the independent variables, namely Islamic business ethics (X1) and halal certification (X2) have a significant influence on the dependent variable, namely purchasing decisions (Y).